Microchip Module for Blood Sample Preparation and Nucleic Acid Amplification Reactions - Yuen, Po Ki; Kricka, Larry J.; Fortina, Paolo; Panaro, Nicholas J.; Sakazume, Taku; Wilding, Peter

(untitled) (Genome Research, 2001)
A computer numerical control-machined plexiglas-based microchip module was designed and constructed for the integration of blood sample preparation and nucleic acid amplification reactions. The microchip module is comprised of a custom-made heater-cooler for thermal cycling, a series of 254 μm × 254 μm microchannels for transporting human whole blood and reagents in and out of an 8–9 μL dual-purpose (cell isolation and PCR) glass-silicon microchip. White blood cells were first isolated from a small volume of human whole blood (<3 μL) in an integrated cell isolation–PCR microchip containing a series of 3.5-μm feature-sized “weir-type” filters, formed by an etched silicon dam spanning the flow chamber. A genomic target, a region in the human coagulation Factor V gene (226-bp), was subsequently directly amplified by microchip-based PCR on DNA released from white blood cells isolated on the filter section of the microchip mounted onto the microchip module. The microchip module provides a convenient means to simplify nucleic acid analyses by integrating two key steps in genetic testing procedures, cell isolation and PCR and promises to be adaptable for additional types of integrated assays.